Three-faced Brahma figure - Temples of India Project Team (Jio Institute, 2024)
The three-faced Brahma wears a jatamukuta (crown of matted hair) and carries a shruka (sacrificial ladle) and putaka (water vessel) in the upper arms, along with a kamandalu (water pot) and akshamala (rosary) in the lower arms.